Dampak WCM dan Likuiditas Terhadap Profitabilitas Perusahaan Consumer Non-Cyclicals yang Terdaftar di BEI tahun 2021-2023 - Yayan Kurniasari; Ika Yoga (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to investigate how working capital management (WCM) and liquidity affect the profitability of consumer non-cyclical companies listed on the Indonesia Stock Exchange (IDX). The population of this study is all consumer non-cyclical companies listed on the IDX. Sample selection with the criteria of companies that publish financial reports for the period 2021-2023 with a sample of 75 companies with a total of 225 observations. This study uses panel data regression analysis techniques. The dependent variable of this study is Return on Asset (ROA) which can represent the company's profitability. The independent variables used are Working Capital Management (WCM) which is proxied by CCC, ARP, APP, ICP and liquidity which is proxied by CR. The results of this study indicate that the Cash Conversion Cycle (CCC), Payables Period (APP), and Current Liabilities (CR) have a significant positive effect on ROA. While the Receivables Period (ARP) and Inventory Conversion Period (ICP) have a significant negative relationship to ROA. This study has limitations in that it only uses samples from one industrial sector and the period between 2021-2023.